Exocrine gland-resident memory CD8+ T cells use mechanosensing for tissue surveillance - Ruef, Nora; Martínez Magdaleno, Jose; Ficht, Xenia; Purvanov, Vladimir; Palayret, Matthieu; Wissmann, Stefanie; Pfenninger, Petra; Stolp-Rastätter, Bettina; Thelen, Flavian; Barreto de Albuquerque, Juliana; Germann, Philipp; Sharpe, James; et al. (Science immunology, 2023)
Tissue-resident CD8+ T cells (TRM) continuously scan peptide-MHC (pMHC) complexes in their organ of residence to intercept microbial invaders. Recent data showed that TRM lodged in exocrine glands scan tissue in the absence of any chemoattractant or adhesion receptor signaling, thus bypassing the requirement for canonical migration-promoting factors. The signals eliciting this noncanonical motility and its relevance for organ surveillance have remained unknown. Using mouse models of viral infections, we report that exocrine gland TRM autonomously generated front-to-back F-actin flow for locomotion, accompanied by high cortical actomyosin contractility, and leading-edge bleb formation. The distinctive mode of exocrine gland TRM locomotion was triggered by sensing physical confinement and was closely correlated with nuclear deformation, which acts as a mechanosensor via an arachidonic acid and Ca2+ signaling pathway. By contrast, naïve CD8+ T cells or TRM surveilling microbe-exposed epithelial barriers did not show mechanosensing capacity. Inhibition of nuclear mechanosensing disrupted exocrine gland TRM scanning and impaired their ability to intercept target cells. These findings indicate that confinement is sufficient to elicit autonomous T cell surveillance in glands with restricted chemokine expression and constitutes a scanning strategy that complements chemosensing-dependent migration.